Tourist Farm Service Quality Assessment - Pažek , Karmen; Rozman , Črtomir (Journal for Geography, 2010)
Farm tourism shows a structure different from agriculture, forestry, and fishery; farm tourism is expanding, labour intensive, generates an influx of money, and maintains the service base in the region. Farm tourism is one of the most important supplementary activities and generates considerable secondary income. This paper presents the developed methodology that will enable the ranking of tourist farms based on their service quality. This is accomplished through the use of the expert system based on the DEXi decision-making method. Using DEXi, the multi-criteria decision model for the assessment of farm tourism's service quality was developed. The model was applied in practice on 7 vacation farms. The data from the questionnaires completed by farm guests and hosts was used as input data in the multi-attribute model and as an arbitrary estimation for the farm. The results of the model are shown as the assessments for individual farms. Out of seven chosen farms, four achieved the best possible estimation. Two of them achieved middle estimation. For the last tourist farm, where a data deficit was present, the model showed two final possible estimations (very good or good and bad - depends on value of missing attributes).